2005
DOI: 10.4102/jsava.v76i2.404
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary AA amyloidosis, hepatocyte dissociation and multinucleated hepatocytes in a 14-year-old free-ranging lioness (Panthera leo)

Abstract: A 14-year-old lioness, originating from Etosha in Namibia, and a member of a pride in Pilanesberg National Park since translocation in 1994, was euthanased due to fight-related vertebral fracture and spinal injury, incurred approximately 6-8 weeks previously. Blood specimens collected at the time of death showed mild anaemia and a leukogram reflecting stress and chronic infection. Necropsy conducted within 2 hours of death was on a dehydrated, emaciated animal with hindquarter wasting and chronic traumatic fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…To date, 2 studies have described the histological features of renal amyloidosis in lions. Williams et al 39 reported amyloidosis characterized by proximal medullary interstitial amyloid deposits in a 14-year-old lion from Namibia (originally a wild animal). Newkirk et al 21 described a case of amyloidosis in an 18-year-old captive lion characterized by localized amyloid deposition in the corticomedullary border of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 2 studies have described the histological features of renal amyloidosis in lions. Williams et al 39 reported amyloidosis characterized by proximal medullary interstitial amyloid deposits in a 14-year-old lion from Namibia (originally a wild animal). Newkirk et al 21 described a case of amyloidosis in an 18-year-old captive lion characterized by localized amyloid deposition in the corticomedullary border of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Dağılımına göre sistemik ve lokal, patogenezine göre primer ve sekonder olarak sınıflandırılmaktadır [2] . Amiloidoz yabani hayvanlardan Sibirya kaplanlarında, vizonlarda (mink), siyah bacaklı kediler ve siyah bacaklı gelinciklerde [2] , çitalarda [3] , Dorcas ceylanında [4] , Arap ceylanında [5] , dağ ceylanında [6] , Rocky dağı büyük boynuzlu koyunlarında [7] , tavşanlarda [8] , aslanlarda [9] , kuğularda ve kınalı kekliklerde [10,11] , deniz aslanı [12] , yunus [13] ve balinalarda [14] bildirilmiştir.…”
unclassified
“…Chronically elevated SAA concentrations are a prerequisite for the pathogenesis of secondary amyloidosis, a progressive and fatal disease characterised by the deposition of insoluble unbranched fibrils composed principally of proteolytically cleaved SAA in major organs (Jensen and Whitehead, 1998). AA amyloidosis is a common disease and has been reported in a number of species (Cowan, 1995;Gruber and Linke, 1996;Papendick et al, 1997;Schulze et al, 1998;Ludlage et al, 2005;Williams et al, 2005), including domestic animals (Guo et al, 1996;van der Linde-Sipman et al, 1997;Landman et al, 1998;Mensua et al, 2003;Shtrasburg et al, 2005;Tojo et al, 2005) such as goose (Szabó et al, 2000).…”
mentioning
confidence: 99%